2010
DOI: 10.1016/j.jaci.2010.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab as a corticosteroid-sparing agent in lymphocytic variant hypereosinophilic syndrome

Abstract: Background-Mepolizumab, a monoclonal anti-interleukin-5 (IL-5) antibody, is an effective corticosteroid-sparing agent for patients with F/P-negative hypereosinophilic syndrome. Lymphocytic variant hypereosinophilic syndrome (L-HES) is characterized by marked overproduction of IL-5 by dysregulated T-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 22 publications
3
84
0
Order By: Relevance
“…T-cell clonality was determined in peripheral blood by PCR of T-cell receptor (TCR)-γ rearrangement patterns. 15 Additional studies to assess end organ involvement were performed as clinically indicated.…”
Section: Baseline Clinical Assessment Of Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell clonality was determined in peripheral blood by PCR of T-cell receptor (TCR)-γ rearrangement patterns. 15 Additional studies to assess end organ involvement were performed as clinically indicated.…”
Section: Baseline Clinical Assessment Of Study Subjectsmentioning
confidence: 99%
“…Serum CCL17/TARC (R&D) and total serum tryptase were quantified as previously described. 15,16 Stem cell factor (SCF) was assessed by an enzyme-linked immunosorbent assay according to the manufacturer's (R&D) instructions; the limit of detection was 9 pg/mL. Total serum IgE levels were determined by ImmunoCAP (Phadia).…”
Section: Serological Assessmentsmentioning
confidence: 99%
“…In addition to its robust circulating eosinophil reduction capacity, anti-IL-5 antibody also demonstrated ex vivo efficacy (Stein et al, 2008). The anti-IL-5 therapy proved to be effective in controlling hypereosinophilic syndrome in terms of eosinophil count reduction and steroid sparing Roufosse et al, 2010;Garrett et al, 2004). Furthermore, anti-IL-5 therapy also demonstrated promising effectiveness in reducing tissue eosinophilia in eosinophilic esophagitis (EoE) (Assa'ad et al, 2011;Spergel et al, 2012), a type of eosinophilic disorder in the upper GI tract.…”
Section: Regulation Of Eosinophils Eosinophil Development (Hematopoiementioning
confidence: 99%
“…Furthermore, almost half of the patients receiving mepolizumab were durably tapered off CS until the end of the study. Exploratory investigations conducted during this trial identified a subset of patients with L-HES, and their response to IL-5-targeted therapy was compared with that of patients with normal T-cell phenotyping studies [66]. Mepolizumab showed similar efficacy in both groups in terms of CS-sparing, although a lower proportion of patients with L-HES maintained eosinophil levels below 600/µl throughout the study.…”
Section: Antibodies Targeting Il-5mentioning
confidence: 99%